REAL MORAL EDUCATION FOR A VIRTUAL YOUNG PEOPLE - Raquel Rosan Christino Gitahy (Travessias, 2007)
The present article reflects young the moral attitude of front to the virtual environment. The reflection on our object of study imposes to define them who is this young influenced for the virtual, present world in the pertaining to school banks, and also demands that if it evaluates which the responsibility of the school in the formation of the technological being. As referencial theoretician we use Morin, for the definition of the social being and Piaget, for the concepts of autonomy and heteronomia. Based in these theories we initiate the field research observing one hundred young while they were in two locus virtual: in the games and the InterNet. The choice for these locus was given therefore has a bigger frequency of the virtual young in the same ones. As result of our research we can perceive that during the computer games the young does not interact, but has only one reactivity, therefore the determined relation action-reaction or same adequacy has a limitation inputs that they necessarily generate always and outputs. It does not have an exchange situation that allows acting criticamente, making possible a bidirecionalidade in the communication process, thus inexisting the interatividade, base for the desirable moral development: the autonomous worker. In relation to locus InterNet, that theoretically makes possible an interaction, therefore he has a reciprocal relationship, what he exists, in he practises, it is the anonymity, blocking such possibility. Still in relation the InterNet one another negative aspect to point out is that it does not have conditions so that the procedures of construction of the moral autonomy if carry through, because the activities, the reactions already are foreseen in the